Enhancing Affective Commitment among Millennial Employees: The Role of Organizational Embeddedness, Perceived Organizational Support, and Work Engagement - Shaqila Caesarine Mulachela Mulachela; Aryana Satrya (Eduvest - Journal of Universal Studies, 2024)
The tight labor market competition afforces organizations to find the right strategies to address the issue of low employee resistance, one way being to enhance affective commitment among employees towards the organization they work for. This study employs Social Exchange Theory (SET) to examine the influence of organizational embeddedness and perceived organizational support on affective commitment and the indirect influence through work engagement mediation. Empirical data were collected from 332 millennial generation employees in Indonesia using an online survey assessed through a 7-point Likert scale. The study was analyzed using Structural Equation Modeling (SEM) and confirmatory factor analysis to test seven proposed hypotheses. The study's findings indicate that organizational embeddedness and perceived organizational support are positively related to affective commitment both directly and through work engagement mediation. This research is expected to contribute to human resource policy-making to enhance affective commitment among millennial generation employees in Indonesia.